2012
DOI: 10.1093/aob/mcs066
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary gene flow and mating system of Arabis alpina in a Central European alpine landscape

Abstract: In the alpine landscape studied, genetic structure occurred on small spatial scales as expected for alpine plants. However, gene flow also covered large distances. This makes it plausible for alpine plants to spread beneficial alleles at least via pollen across landscapes at a short time scale. Thus, gene flow potentially facilitates rapid adaptation in A. alpina likely to be required under ongoing climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 61 publications
4
61
0
Order By: Relevance
“…Whereas most studies emphasize adaptation across large spatial scales, we show that differentiation can occur between neighbouring populations with limited isolation by distance and possibly extensive gene flow (e.g. Alberto et al ., ; Buehler et al ., ). General support for adaptation was found in terms of plant survival but not for reproductive output (contrary to Hereford, ).…”
Section: Discussionmentioning
confidence: 97%
“…Whereas most studies emphasize adaptation across large spatial scales, we show that differentiation can occur between neighbouring populations with limited isolation by distance and possibly extensive gene flow (e.g. Alberto et al ., ; Buehler et al ., ). General support for adaptation was found in terms of plant survival but not for reproductive output (contrary to Hereford, ).…”
Section: Discussionmentioning
confidence: 97%
“…; Buehler et al. ), so that a particular allele may rapidly spread once established and hence mask adaptive patterns. In order to confirm such a hypothesis of local adaptation, more locations on a small spatial scale would have to be sampled in the original study areas in the Swiss as well as the French Alps (Buehler et al.…”
Section: Discussionmentioning
confidence: 99%
“…Within each location, we searched for A. alpina occurrences in each of the three distinct habitat types, situated at 0.14-3.3 km distance. Buehler et al (2012) showed that median pollen dispersal in A. alpina is about 20 m, but that exceptional long-distance dispersal of pollen up to 1 km is possible. The spatial separation of sampled habitat types within a location should therefore only allow for rare gene flow by pollen.…”
Section: Sampling Design Of the Independent Validation Data Setmentioning
confidence: 99%
“…The generally extreme nature of alpine environments has in some cases selected for alpine specialization, and speciation itself may be accelerated in alpine habitats [33], [41][44]. The ecological differences between lowland and alpine environments can affect patterns of dispersal, rates of population divergence, and speciation [41], [45][47]. The isolation of mountain tops amongst intervening temperate environments can reinforce this differentiation through restricted gene flow [45][49].…”
Section: Introductionmentioning
confidence: 99%